A Guarantee System for Youth Policies. "One Step Ahead" Towards employment and autonomy - Federighi, Paolo; Torlone, Francesca (Proceedings e report, 2013)
The study examines a vast panorama of the policies on which depend the living and working conditions of young people. Measures were examined that can be enacted on a regional level starting from the concrete experience of 6 Regional Governments in as many European countries. The book shows that a true "Youth Guarantee" must guarantee support for the complexity of the transitions that characterise young person's life and shows how this must be adapted to the different conditions the various segments of young population live in. The wealth and variety of concrete experiences offered by regional policies show how it is possible to activate public ations that, having adequate ingredients, will be able to lessen the negative effects of the economic crisis and allow young people to take one step ahead at any time in their private and professional life.